The Routledge handbook of public speaking research and theory - Munz, Stevie M.; McKenna-Buchanan, Tim; Wright, Anna M. (College teacher) (New York, NY : Routledge, 2024)
"Providing a comprehensive survey of the empirical research, theory, and history of public speaking, this handbook fills a crucial gap in public speaking pedagogy resources and provides a foundation for future research and pedagogical development. Bringing together contributions from both up-and-coming and senior scholars in the field, this book offers a thorough examination of public speaking guided by research across six key themes: the history of public speaking, the foundations of public speaking, issues of diversity, equity, inclusion, considerations of public speaking across contexts, assessment of public speaking, and the future of public speaking in the 21st century. The evidence-based chapters engage with a broad discussion of public speaking through a variety of viewpoints to demonstrate how subtopics are connected and fraught with complexity. Contributors explore public speaking in education, business and professional settings, and political contexts, and outline how skills learned through public speaking are applicable to interpersonal, small group, and business interactions. Reinforcing the relevance, importance, and significance of public speaking in individual, interpersonal, social, and cultural communication contexts, this accessibly written handbook will be an indispensable resource for public speaking instructors and program administrators. It will also be valuable reading for Communication Pedagogy and Introduction to Graduate Studies courses"--
Introduction / Joshua N. Westwick, Sherwyn P. Morreale, and Stevie M. Munz -- A historical tracing of public speaking pedagogy / Joseph P. Zompetti -- Canons of rhetoric : building blocks for speech construction / Adrienne E. Hacker-Daniel and Christopher J. Oldenberg -- Public speaking and theatre : a joint tradition / Kyle A. Hammonds -- Public speaking and democratic life : a neo-classical rhetoric for the digital age / J. Michael Hogan -- The instruction of public speaking : an index of major events in the communication discipline and related trends within the literature / Maura R. Cherney -- A communication traits approach to the teaching and learning of public speaking / Scott A. Myers, Jordan Atkinson, Stephen M. Kromka, Sara Pitts, and Melissa F. Tindage -- Ethical concerns in public speaking / Sara V. A. Kaufman -- Listenability : the art of meaningful public speaking / Tim McKenna-Buchanan and Mary Lahman -- Audience analysis in public speaking : a comprehensive exploration / Jackson W. Scott, Madalena Robertson, and Nicholas T. Tatum -- Rhetorical audience analysis and reception studies of public speaking / Jens E. Kjeldsen -- Approaches to organizing and outlining in public speaking / Maria Hannah and Carly Densmore -- Delivery modes, elements, and exceptions : exploring and troubling the canon of delivery in public speaking / Justin J. Rudnick, Douglas Roberts, Tennisha Sonsalla, Vanessa Fowler, and Caleb Webb -- Verbal and nonverbal communication : creating inclusion and accessibility / Miranda N. Rouse, Kent R. Schafer, Darrin J. Griffin, and Cassidy Duncan -- A clearer picture : the history of visual aids in public speaking / Adam C. Jones and Anna M. Wright -- Persuasive public speaking : considerations for a post-truth era / Josh Fitzgerald, Kevin R. Meyer, and Stephen K. Hunt -- Exploring speech anxiety : managing our nerves to share our stories / Suzy Prentiss and Dakota Horn -- Viva lost vagus : yogic breathing, neuroscience, and public speaker anxiety / Eddie Glenn -- Relevant today and prepared for tomorrow : inclusion, diversity, equity, access (IDEA) in public speaking / Kristina Ruiz-Mesa and Melissa A. Broeckelman Post -- Accents and dialects in public speaking / Kallia O. Wright, Luisa M. Cotto, and Zixiao Yang -- Critical race theory interventions for public speaking / Sergio Fernando Jaurez and C. Kyle Rudick -- Whiteness and public speaking / Kristen P. Treinen -- Revisiting public speaking as a liberal art at Hispanic serving institutions / Cyndi Grobmeier and W. Bradford Mello -- Accommodations in the public speaking classroom for students with mental health conditions / Jillian Joyce Kaufmann -- Access and accommodation and public speaking / Robbie D. Hall and Darcy L. Wente-Hahn -- Building communication competence through public speaking : considerations for faculty outside of the communication discipline / Amy May and Victoria McDermott -- Public speaking's transferable skills for industry / Michael E. Burns and Joshua H. Miller -- Public speaking in business and professional settings / Caroline Walbuesser and Francis Brandau -- Public speaking in K-12 contexts : not quite uncharted waters / Michael G. Strawser, David A. Yastremski, and Carly Densmore -- Democratic education through public speaking / Gabriel Wisnewski-Parks and Vincent Russell -- Public speaking in action : forensics as an extended classroom for skills on democratic participation and advocacy / Kristopher Copeland and Ant Woodall -- Measuring student learning in a college level public speaking class : the development and evolution of a rubric / Cheri Simonds and John Hooker -- Assessment for learning in public speaking education : best practices for design, implementation, and continuous improvement / Karla M. Hunter -- A critical systematic review of rubric research in the public speaking classroom / Drew T. Ashby-King, Lindsey B. Anderson, and Melissa A. Lucas -- Speaking soundly : post-colonial approaches for the future of public speaking / Sidi Becar Meyara -- Online speaking : adapting to the virtual environment / Brent Kice -- Online and mediated public speaking / Pat J. Gehrke -- The case for online public speaking skills in the communication curriculum / Nick Linardopoulos -- Digital resources for public speaking / Jeffrey H. Kuznekoff -- Where we go from here : concluding remarks / Stevie M. Munz, Anna M. Wright, and Tim McKenna-Buchanan.
Keywords: Public speaking -- Handbooks, manuals, etc; Public speaking -- Research; LANGUAGE ARTS & DISCIPLINES / Public Speaking; EDUCATION / Research